2014
DOI: 10.1177/0300060514528483
|View full text |Cite
|
Sign up to set email alerts
|

Measuring both procalcitonin and C-reactive protein for a diagnosis of sepsis in critically ill patients

Abstract: Background: The usefulness of procalcitonin (PCT) and C-reactive protein (CRP) as individual biomarkers, and in combination, for the identification of infections in a critically ill patient cohort was evaluated retrospectively. Methods: Best cut-off values for PCT and CRP for a diagnosis of sepsis in critically ill patients were determined using receiver operator characteristic (ROC) curve analysis. Both combined tests and individual tests were performed for PCT and CRP, with positive and negative results reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Therefore, the levels of CRP were in accordance with the severity of organ function. The same results were also reported in a research conducted by Hong-Xiang et al 16 Table 3 showed that the largest group (40.5%) was the samples of sepsis patients with RNL above 5 and CRP levels between 100-200. This indicated that sepsis in this research was most often caused by a bacterial infection.…”
supporting
confidence: 86%
“…Therefore, the levels of CRP were in accordance with the severity of organ function. The same results were also reported in a research conducted by Hong-Xiang et al 16 Table 3 showed that the largest group (40.5%) was the samples of sepsis patients with RNL above 5 and CRP levels between 100-200. This indicated that sepsis in this research was most often caused by a bacterial infection.…”
supporting
confidence: 86%
“…There is a notable increase of CRP level 4-6 h after stimulation. These levels double every 8 h and peak 36 to 50 h after an infection/inflammation stimulus [14] . CRP measurement is cheap and rapidly available, but increases of CRP levels are unspecific, since they can be observed, i.e., after surgery or trauma [15] .…”
Section: Crp and Pctmentioning
confidence: 99%
“…2 C-reactive protein (CRP) is generally considered a helpful marker for diagnosis of sepsis used in addition to blood culture, but sometimes it may be inadequate for sepsis diagnosis, so more rapid efficient markers are needed. 3 CRP is an acute phase protein synthesized in liver in the presence of infectious and/or inflammatory stimuli, correlating with the disease severity, 4 but its production significantly varied during the neonatal period, 5 with lower production in preterm compared to full term neonates. 6 The high sensitivity assays of CRP (hsCRP) could detect lower grade of inflammation.…”
Section: Introductionmentioning
confidence: 99%